Investigation of a Basic Dye Adsorption Characteristics of a Non-Living Submerged Aquatic Plant (Myriophyllum spicatum) - BASIBUYUK, MESUT; SAVCI, SERPIL; KESKINKAN, OLCAYTO; EKREM CAKMAK, MEHMET (Asian Journal of Chemistry, 2010)
In this paper, the adsorption properties of Myriophyllum spicatum (Eurasian watermilfoil) for a basic dye (basic blue 41) were investigated as a biosorbent and the results were compared with other biosorbents. Data obtained from the initial batch adsorption studies have indicated that dried M. spicatum is capable of removing basic blue 41 from the solution. The dye biosorption was fast and equilibrium was attained within 20 min. Data obtained from further batch studies applied to Langmuir and Freundlich Models. High correlation coefficient with Linearized Langmuir Model was observed, however, negative qmax value was observed indicating the inadequacy of Langmuir model. High correlation coefficient was also obtained with application of linearised form Freundlich model and it was found more suitable for the dye plant system. The kinetics of adsorption of basic blue were also analyzed and rate constants were derived for various dye concentrations. Initial part of the adsorption was found to be governed by film diffusion process. It was also found that the overall adsorption process was best described by the pseudo second order kinetics. Gibbs free energy value was found to be -2.2793 kJ and indicating the spontaneity of the system. The results showed that this submerged aquatic plant M. spicatum can be successfully used for the removal of basic blue 41.